42nd SIAN National Congress - May 6,7,8, 2024, Riccione: Nephrology Nursing: Role, Competencies, Sustainability. (Dissertation Nursing, 2025)
Report of the 42nd SIAN (Society of Nephrology Area Nurses) National Congress held on May 6,7,8, 2024, in Riccione, Italy.The Congress, through plenary expositions and workshops, covered the following topics, reported here:- Renal Genetic Diseases- Competencies of the nephrology and dialysis nurse in the international context- Self Care And Technology In Hemodialysis- Renal Transplantation Between Tradition and Innovation. New tools for long-term care- Areas of focus and the nephrology and dialysis nurse's skill acquisition pathway in Italy- Literature reviews and practical exercises within primary literature databases- The Family Nurse in Peritoneal Dialysis: experience ASST NORD MILAN- Territorial management of peritoneal dialysis: the possible areas of intervention of the Family and Community Nurse- Digitization and Information Technology. Information systems serving peritoneal dialysis specialist nursing care- Peritoneal Dialysis and Artificial Intelligence.- Peritoneal Dialysis Yesterday and Today- Green Nephrology